2014
DOI: 10.1080/02614367.2014.893005
|View full text |Cite
|
Sign up to set email alerts
|

Questioning policy, youth participation and lifestyle sports

Abstract: Young people have been identified as a key target group for whom participation in sport and physical activity could have important benefits to health and wellbeing and consequently have been the focus of several government policies to increase participation in the UK. Lifestyle sports represent one such strategy for encouraging and sustaining new engagements in sport and physical activity in youth groups, however, there is at present a lack of understanding of the use of these activities within policy contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…These strategies include mixing teams (for example across talent, gender, age), downplaying competition, overlapping players and spectators and putting on various events in the same space. Academic research on activities including parkour [40][41][42], skateboarding [41,42] mountain-biking [12] and surfing [13,38] has demonstrated the potential of more informal, non-competitive and youth-led activities to engage those young people disenfranchised by traditional competitive team sports. In the UK, Hignett, et al [13] recently published work that found significant benefits in engaging in a surfing program among vulnerable school aged children, at risk of being excluded from school (see also [43]).…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include mixing teams (for example across talent, gender, age), downplaying competition, overlapping players and spectators and putting on various events in the same space. Academic research on activities including parkour [40][41][42], skateboarding [41,42] mountain-biking [12] and surfing [13,38] has demonstrated the potential of more informal, non-competitive and youth-led activities to engage those young people disenfranchised by traditional competitive team sports. In the UK, Hignett, et al [13] recently published work that found significant benefits in engaging in a surfing program among vulnerable school aged children, at risk of being excluded from school (see also [43]).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados de distintas investigaciones sugieren que tales actividades se asocian con el desarrollo positivo en estas franjas de edad (Leversen, Danielsen, Birkeland y Oddrun, 2012;King y Church, 2015), entendiendo el desarrollo (social y emocional) como un proceso madurativo, de crecimiento e incremento de la autonomía. Sin embargo, la capacidad de participación y la autonomía no es un resultado garantizado que derive espontáneamente del trán-sito de la infancia a la adolescencia y juventud (Deci y Ryan, 2000).…”
Section: Introductionunclassified
“…The regulation and policy incorporation of lifestyle sports, if not managed properly, can deprive them of "the mimetic properties which make them so attractive to participants in the first instance" (Turner 2013, 1259), particularly to those who are alienated by more traditional and formalised sport provision (Tomlinson et al 2005, King andChurch 2015). xii It is therefore vital to enable participants' ownership and control over the institutionalisation of their practice (Gilchrist and Wheaton 2011).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…policies entails important challenges with regard to defining safety regulations and providing suitable forms of governance for an activity that was born as an alternative to mainstream sports (Tomlinson et al 2005, King andChurch 2015). While the normalisation of the practice is partly achieved through its spatial containment within parkour-parks (Gilchrist and Osborne 2017) and other forms of indoorisation (Van Bottenburg and Salome 2010), a further measure to ensure its safety is the introduction of teaching/coaching qualifications Wheaton 2011, O'Loughlin 2012).…”
Section: Teaching/coaching Qualifications and The Contested Institutimentioning
confidence: 99%
See 1 more Smart Citation